The Quest for Syntony: Democracy and Regionalism in South America - Ramanzini Junior, Haroldo (2021)
This article analyses how the issue of democracy protection has been incorporated into South American regionalism. It shows the motivation for building Democracy Clauses in regionalism and identify the challenges for its implementation. From 1985 to 2008, there was a progressive insertion of instruments related to democracy protection. Between 2009 and 2015 efforts were aimed at expanding regional autonomy to deal with political crises. As of 2016-2020 democracy has been used as an element of division between states. We identify the factors that help explain the changes observed which have resulted in the weakening of regionalism's contribution to democracy.